Analisis Kebutuhan Ruang Parkir Berdasarkan Lama Parkir Akibat Perluasan Bandara Internasional Sultan Hasanuddin - Panjaitan, Maradona; Mallawangeng, Tamrin; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Sultan Hasanuddin International Airport experienced an average growth in passengers and aircraft movements for the 2014-2018 period, respectively 11.35% and 9.29% per year. Therefore, in order to improve service, airport development is being carried out referring to the Sultan Hasanuddin Airport Master Plan, including a parking building for 4-wheelers with a capacity of 624 SRP, while the existing 4-wheeled parking capacity is 1,072 SRP. So that data was collected on the number of passengers during peak hours, data on the number of vehicles and data on the duration of each vehicle's parking in 2018 before the airport development was carried out. From these data, a calculation of the need for parking space is carried out during peak hours as well as a calculation of the availability and need for parking space based on the length of time each vehicle is parked. So that the need for parking space during peak hours is 1,183 SRP, and the required capacity based on the characteristics of the length of time each vehicle is parked is 989 SRP/hour. While currently being developed is 624 SRP with a capacity based on the long parking characteristics of each vehicle is 522 SRP./hour. From the results of these calculations it can be concluded that the development of stage 1 is not able to serve parking needs during peak hours, so that additional parking space capacity is needed.